2016
DOI: 10.1111/jsr.12427
|View full text |Cite
|
Sign up to set email alerts
|

Development of nap neurophysiology: preliminary insights into sleep regulation in early childhood

Abstract: SUMMARY Although all young children nap, the neurophysiological features and associated developmental trajectories of daytime sleep remain largely unknown. Longitudinal studies of napping physiology are fundamental to understanding sleep regulation during early childhood, a sensitive period in brain and behaviour development and a time when children transition from a biphasic to a monophasic sleep–wakefulness pattern. We investigated daytime sleep in eight healthy children with sleep electroencephalography (EE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 36 publications
(58 reference statements)
7
25
0
Order By: Relevance
“…In a recent review of over 300 children, Karaoui et al have demonstrated the safety and efficacy of chloral hydrate for use in paediatric sedation 36 . Children were scanned 15-20 min after sleep onset, as a comparable stage of slow wave sleep was achieved within this timeframe as during an afternoon nap 37 . The experimental design and the analyses used controlled for any potential confounding effects of chloral hydrate on MRS measures.…”
Section: Image Acquisitionmentioning
confidence: 99%
“…In a recent review of over 300 children, Karaoui et al have demonstrated the safety and efficacy of chloral hydrate for use in paediatric sedation 36 . Children were scanned 15-20 min after sleep onset, as a comparable stage of slow wave sleep was achieved within this timeframe as during an afternoon nap 37 . The experimental design and the analyses used controlled for any potential confounding effects of chloral hydrate on MRS measures.…”
Section: Image Acquisitionmentioning
confidence: 99%
“…We conducted our nap assessments in-home in both TD children and children with DS, allowing for as natural an examination of naps and learning as possible. Very few studies have examined the underlying mechanisms of napdependent learning in young children, and often the sleep physiology has been conducted in a laboratory setting, which may limit the acquisition of natural naps containing REM (36). The feasibility of ambulatory PSG has been extensively documented in special populations such as individuals with DS (37,38) and children with autism spectrum disorder (39) as well as in typically developing young children as early as 2 y (40,41).…”
Section: Assessment Of Nap Physiologymentioning
confidence: 99%
“…Little is known, however, about the development of ultradian cycling in early childhood, a period of significant change in sleep behavior, including a decline in total sleep duration, the elimination of daytime naps, and the emergence of behavioral sleep problems (Beltramini and Hertzig, 1983; Zuckerman et al, 1987; Iglowstein et al, 2003; Acebo et al, 2005; Crosby et al, 2005; Honaker and Meltzer, 2014). Preschool children may also exhibit REM sleep during midday naps (Kurth et al, 2016), reflecting an absence of the strong circadian gating of REM sleep observed in adults (Czeisler et al, 1980; Dijk and Czeisler, 1995). Furthermore, dysregulation of REM sleep and ultradian cycling may be related to affective disorders in school-age children and adolescents (Ivanenko et al, 2005), which is consistent with observed associations between these measures in adults (Benca et al, 1997).…”
mentioning
confidence: 99%